Financial Performance Analysis Using Economic Value Added (EVA) Method and Economic Rentability of PT Bumi Resources Tbk - Irma Setyawati (Enrichment : Journal of Management, 2021)
This research aims to analyze financial developments to find out how companies measure the level of achievement of Economic Value Added (EVA) and the amount of economic rentability in PT Bumi Resources Tbk salama period 2018-2021. The type of data collected is in the form of quantitative data in the form of data on figures such as financial statements (balance sheets & income statements). The data source used is secondary data to explain the results of the calculation of Economic Value Adedd (EVA) and economic rentability. The results of this study explained that the EVA level and the resulting economic rentability rate were not able to reach the standard so that in 2018 to 2021 the performance of PT Bumi Resources Tbk was not good.